MAHKAMAH AGUNG DAN SUPREMASI KONSTITUSI: DISKRESI YUDISIAL DALAM PENERAPAN UNDANG-UNDANG - Titon Slamet Kurnia (Mimbar Hukum, 2022)
Abstract This article aims to discuss the role of the Supreme Court in defending the principle of the supremacy of the constitution. The discussion finds that the Supreme Court has inherent judicial authority to defend the supremacy of the constitution over legislation even though the Constitution itself does not confer the authority explicitly. This article uses conceptual or theoretical and comparative approaches. Constitution supremacy is a fundamental constitutional principle that binds all public authorities of the State. As part of the public authorities, the Supreme Court must disregard unconstitutional legislation. To do this the Supreme Court has judicial discretion to set aside legislation whenever it assumes that the legislation in question is contrary to the Constitution before it can be applied in a concrete case. Unlike the Constitutional Court, the Supreme Court does not have the authority to invalidate unconstitutional legislation. The Supreme Court may assess the constitutionality of legislation in the sense of weak-form judicial review. Whereas the Constitutional Court’s authority to review the constitutionality of legislation is a strong-form judicial review. The two models of judicial review should work together because Indonesia adopts the supremacy of the constitutional principle, instead of the supremacy of the Constitutional Court. Abstrak Artikel ini bertujuan hendak mendiskusikan peran Mahkamah Agung dalam mempertahankan asas supremasi konstitusi. Hasil dari diskusi tersebut adalah Mahkamah Agung memiliki kewenangan yudisial inheren dalam mempertahankan supremasi konstitusi terhadap undang-undang meskipun Konstitusi sendiri tidak memberikan kewenangan eksplisit. Artikel ini menggunakan pendekatan teoretis atau konseptual dan pendekatan perbandingan. Supremasi konstitusi adalah asas konstitusional fundamental yang mengikat seluruh badan pemerintah. Sebagai bagian dari badan pemerintah, Mahkamah Agung memiliki diskresi yudisial untuk mengesampingkan undang-undang manakala dia beranggapan bahwa undang-undang tersebut bertentangan dengan konstitusi sebelum menerapkannya ke dalam kasus konkret. Tidak seperti Mahkamah Konstitusi, Mahkamah Agung tidak memiliki kewenangan untuk menyatakan undang-undang tidak memiliki kekuatan mengikat. Mahkamah Agung dapat menilai konstitusionalitas undang-undang dalam pengertian weak-form judicial review. Sementara kewenangan Mahkamah Konstitusi untuk menguji konstitusionalitas undang-undang adalah strong-form judicial review. Kedua model pengujian yudisial tersebut seyogianya berjalan bersama karena Indonesia mengadopsi asas supremasi konstitusi, ketimbang supremasi Mahkamah Konstitusi.